Pengaruh Pendapatan dan Sosial Ekonomi Terhadap Kesejahteraan Keluarga Pada Rumah Industri Pengrajin Songket di Kabupaten Aceh Besar - Marwiyati; Safitri, Winny Dian; Nabila, Syifa (Jurnal Ilmiah Basis Ekonomi dan Bisnis, 2025)
This study aims to determine the effect of income and socioeconomic factors on family welfare in the home based songket weaving industry in Aceh Besar Regency. The research employs a quantitative method using primary data collected through questionnaires distributed to 30 songket weavers in Aceh Besar Regency. The sampling technique used in this study is non-probability sampling, specifically the saturated sampling (census) technique. This technique was chosen because all members of the population were included as research samples. Data analysis was carried out using the Partial Least Square (PLS) method. The results of this study indicate that income has a significant effect on family welfare in the home-based songket weaving industry in Aceh Besar Regency. Socioeconomic factors also have an influence on family welfare in the same context. Furthermore, income and socioeconomic factors simultaneously have a positive effect on family welfare among songket weaving households in Aceh Besar Regency. These findings recommend enhancing income levels and improving socioeconomic conditions to support the sustainable welfare of songket artisans’ families. Keywords: Income, Socioeconomic, Welfare, Songket Home Industry